2021
DOI: 10.1016/j.nicl.2020.102531
|View full text |Cite
|
Sign up to set email alerts
|

Temporal-thalamic and cingulo-opercular connectivity in people with schizophrenia

Abstract: Highlights People with schizophrenia show increased thalamo-temporal functional connectivity. People with schizophrenia also show reduced cingulo-opercular connectivity. Thalamo-temporal findings appear robust, replicating across two samples.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
6
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 66 publications
3
6
0
Order By: Relevance
“… 7–11 Over the past 2 decades, neuroimaging studies have identified widespread functional dysconnectivity in individuals with schizophrenia relative to controls. 12–18 These findings have led to the conclusion that schizophrenia cannot be explained in terms of localized dysfunction within specific brain areas and is better understood as a disruption of network-level functional organization. 19–22 The study of functional brain organization has the potential to identify predictive biomarkers for neurodevelopmental and neuropsychiatric disorders and shed light on their underlying mechanisms.…”
Section: Introductionmentioning
confidence: 99%
“… 7–11 Over the past 2 decades, neuroimaging studies have identified widespread functional dysconnectivity in individuals with schizophrenia relative to controls. 12–18 These findings have led to the conclusion that schizophrenia cannot be explained in terms of localized dysfunction within specific brain areas and is better understood as a disruption of network-level functional organization. 19–22 The study of functional brain organization has the potential to identify predictive biomarkers for neurodevelopmental and neuropsychiatric disorders and shed light on their underlying mechanisms.…”
Section: Introductionmentioning
confidence: 99%
“…The thalamus is an important brain region for information transmission, integration, and pain modulation ( Ploner et al, 2010 ). Specifically, the nostalgia-encoding region within the prefrontal thalamus is the thalamic subregion connected to the prefrontal lobe ( Garibotto et al, 2020 ; Culbreth et al, 2021 ), which is known to be critical for higher cognitive functions ( Mitchell, 2015 ). In contrast, analgesia encoding within the posterior parietal thalamus involves the thalamic subregion connected to the posterior parietal lobe ( Liu et al, 2019 ; Garibotto et al, 2020 ), contributing to multisensory and sensory-motor integration ( Gilissen et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…Currently, thalamocortical dysconnectivity consisting of reduced thalamo-prefrontal and increased thalamo-somatosensory/parietal connectivity is considered a core neurobiological abnormality in schizophrenia [for further reading, see ( 23 , 30 , 31 )]. Recently developed methods to investigate the interconnectivity of the thalamus, cerebellum, and cortex revealed dysconnectivity among the thalamus, cerebellum, and temporal cortex ( 32 , 33 , 34 ), which highlights the widespread involvement of the thalamus in brain activity and suggests the cerebellum as the next key region to investigate.…”
Section: Thalamic Connectivity System Abnormalities In Psychiatric Di...mentioning
confidence: 99%